Increased Expression of RUNX2 and ALP Resulting from a Combination of Propolis Extract and Bovine Bone Graft in Socket Preservation Material - Utari Kresnoadi; Much Nizar; Soekobagiono (Universidade de São Paulo, 2022)
Abstract The aim of this study was to determine the inductive effect of a combination of propolis and BBG extract on RUNX2 and ALP expression in the tooth extraction sockets of Cavia cobaya. Fifty- six Cavia cobaya were divided into four groups: polyethylene glycol (PEG), propolis extract + PEG, BBG + PEG, and propolis extract + BBG + PEG. The lower left incisor was extracted, and the socket subsequently filled with material according to the specific group of which the subject was a member. The subjects were sacrificed on the 14th and 30th days. Immunohistochemical staining was carried out under a light microscope at 400x magnification. Statistical analysis was then carried out by means of One-Way ANOVA and Tukey HSD tests. The mean number of RUNX2 and ALP expressions in each group was significantly different. The highest number of RUNX2 and ALP expressions occurred in the propolis + BBG + PEG group on the 30th day, while the lowest expressions were observed in the control group on the 14th day. A combination of propolis and BBG extract at a concentration of 2% of active substance effectively increases the expression of RUNX2 and ALP in preserving the tooth extraction sockets of Cavia cobaya.